Anwendung von Lean-Prinzipien im Erdbau - Entwicklung eines Baustellenleitstands auf Basis von Virtual Reality - Kirchbach, Kim (Karlsruher Reihe Technologie und Management im Baubetrieb / Institut für Technologie und Management im Baubetrieb, Karlsruher Institut für Technologie (KIT), 2014)
This dissertation deals with the development of a Virtual Reality-based construction site control centre for earth work in consideration of lean management principles. Beside the enhanced availability of information and increased transparency in presentation, a raise in the performance on-site by the use of a digital Kanban system could be proved.